If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 3x + 11 Reorder the terms: 1 = 11 + 3x Solving 1 = 11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + -3x = 11 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + -3x = 11 + 0 1 + -3x = 11 Add '-1' to each side of the equation. 1 + -1 + -3x = 11 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 11 + -1 -3x = 11 + -1 Combine like terms: 11 + -1 = 10 -3x = 10 Divide each side by '-3'. x = -3.333333333 Simplifying x = -3.333333333
| -1/6y=7 | | 4x+4=5(x-4) | | 25=2y-5 | | -12=2(2-x) | | U^4-u^2+36=0 | | -8(3v-5)=23-7v | | -21=n-1 | | b+-2=0 | | 2/3x12= | | 11x=4-2 | | 3x^2+6x+3=18 | | Ax+bx=dx | | -19/16=a/16 | | -1+4x+x-2=12 | | -84=7x | | .2(x+3)-4(2x-3)=-3 | | 128=8(-2x+6) | | 0.5+3.6=4.2-1.5t | | 0.48-0.18x=0.45x-3.3 | | k/13=3 | | -2=x-7-6x | | 6(4x+6)+4(6x+6)+3=48x+64 | | 40+8v=6(1+7v) | | 2y-7=-19 | | .2(x+3)-4(2x-3)=3 | | 7m-4=-9+2m | | x+6=2x-14+11 | | 32x^8y^12/4x^2y | | 15x+14=4(23x+3) | | -6+12k=-90 | | 2x^2-5=-205 | | 1/3(9x) |